The Impact of Corporate Social Responsibility on Company Profitability And Environmental Sustainability - Safitrih, Nurul Amalia; Maulana, Moch Abid Athoillah; Hwihanus, Hwihanus (CV. Lenggogeni Data Publishing, 2024)
Companies use social and environmental issues in their commercial operations as part of the CSR management philosophy. CSR is regarded as both a means of achieving sustainable development and a gauge of a business's overall performance. This study aims to analyze the impact of Corporate Social Responsibility (CSR) on company profitability and environmental sustainability. This research was prepared using a meta-analysis approach, this method combines several studies or journals in a research chosen as the research object. Researchers systematically draw conclusions from journals obtained through international journals regarding